Micropropagation and assessment of genetic stability of Dendrobium transparens Wall. Ex Lindl. using RAPD and ISSR markers - Joshi, Pusp Raj; Pandey, Sushma; Maharjan, Lasta; Pant, Bijaya (Frontiers in Conservation Science, 2023)
Introduction Dendrobium species have been widely used for many health disorders since ancient times. However, due to unrelenting collection to meet the increasing demand for their use in medication and other health products, the natural habitats of medicinal Dendrobium transparens have been devastated and are on the verge of extinction. Methods An efficient in-vitro propagation protocol for Dendrobium transparens using seed derived protocorms was established and genetic homogeneity of the in-vitro regenerants and the wild plant was studied. Results The maximum seed germination was observed in Full strength Murashige and Skoog medium (FMS). Induction of protocorms were achieved on basal as well as half-strength MS medium. The highest number of shoot (11.9 shoots/explant) was achieved in half MS medium fortified with 100 mL/L coconut water in addition with Benzyl amino purine (BAP) 1 mg/L and Kinetin 2 mg/L. Further, elongated shoots were transferred to full and half strength MS root initiating medium supplemented with different concentration of auxins. However, a maximum of (8.3 ± 0.6, 4.9 ± 0.1 cm) roots were achieved in full MS medium fortified with 100 mL/L coconut water and Napthalene acetic acid (NAA) 1.5 mg/L. Ten rapid Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeats (ISSR) primers were used to analyze genetic stability among in-vitro and mother plant. RAPD primers produced a total of 23 fragments while ISSR primers produced a total of 16 fragments. Conclusion The amplified bands of all the samples of in-vitro plants were similar to bands of mother plant. The present research reported here is indicating the applicability of tissue culture for true-to-type plant production and conservation of D. transperens.